Reproductive biology of silurid catfishes Ompok miostoma (Vaillant 1902) in Mahakam River East Kalimantan - Jusmaldi Jusmaldi; Dedy Duryadi Solihin; Ridwan Affandi; MF Rahardjo; Rudhy Gustiano (Masyarakat Iktiologi Indonesia (Indonesian Ichthyological Society), 2019)
Reproductive biology of silurid catfish O.miostoma(Vaillant 1902)as one of endemic species in Mahakam River East Kalimantan is not yet known. This study aimed to analysisreproductive aspect related to changing seasons, including sex-ratio, spawning season, spawning location, length at first gonad maturity, gonado-somatic index, and fecundity. Total fish samples (n=1214)were collected monthly from November 2013 to October 2014 at four locations in the Mahakam River, using many fishing gears.The results of this research showthe total length of fish ranged from 132.19 to 227.30 mm and weight ranged from 20.00 to 70.40 g. The overall sex ratio of male and female was1: 1.56, while at gonad maturity stages were1:1.77. The spawning season range from November to January and peak spawning occurs in December. The highest spawning location was found at swamp flood Semayang Lake. The length at first gonad maturity of male ranged of 191.05-202.60 mm, while it was in 179.56-198.50 female. Maximum average gonado-somatic index (GSI) values obtained for male and female were 0.32 and 2.07 respectively during spawning period in November and declined to minimum in February. The total fecundity and eggs diameter rangedfrom 2648 to 12495 eggsind-1and 0.61 to 1.30 mm respectively. There was a positive correlation between fecundity andtotal length and weightof fishes. Abstrak Biologi reproduksi ikan lais O. miostoma (Vaillant 1902)sebagai salah satu spesies endemik di Sungai Mahakam Kalimantan Timur belum pernah diketahui. Tujuan penelitian ini adalah menganalisisaspek reproduksi ikan laisberkaitan dengan perubahan musimyang mencakupnisbah kelamin, musim pemijahan, lokasi pemijahan, ukuran kali pertama matang gonad, indeks kematangan gonad dan fekunditas.Total ikan contoh 1214 ekor telah dikumpulkan setiap bulan mulai dari bulan November 2013 sampai Oktober 2014di empat lokasi perairan Sungai Mahakam, menggunakan berbagai alat tangkap. Hasil penelitian menunjukkanukuran panjang total ikan berkisar dari 132,19-227,30 mm dan bobot berkisar dari 20,00-70,40 gram.Nisbah kelamin seluruh ikan jantan dan betina yang diamati 1 : 1,56, sedangkanpada tahap kematangan gonad 1:1,77. Musim pemijahan terjadi mulai dari bulan November sampai Januari dan puncak pemijahan pada bulan Desember. Lokasi pemijahan tertinggi ditemukan di rawa banjiran Danau Semayang. Ukuran ikan pertamamatang gonad pada jantan berkisar dari 191,05-202,60 mm dan betina berkisar dari 179,56-198,50 mm. Rata-rata indeks kematangan gonad (IKG) tertinggi ditemukan pada jantan dan betina berturut turut 0,32 dan 2,07 selama musim pemijahanpada bulan November dan menurun hingga terendah pada bulan Februari. Fekunditas total berkisar dari 2.648-12.495 butir telur per individu.Ada korelasi positif antara fekunditas dengan panjang total dan bobot ikan.